Türk romanında ermeniler (1874-2010) - Engin, Ertan (My University, 2010)
Türk romanında Ermenilere hem ulus hem de roman kişisi olarak çok sayıda eserde değinildiğini, yer verildiğini söylemek mümkündür. Yaşam biçimlerinin ve coğrafyanın birbirine yakınlaştırdığı Türk ve Ermeni toplumlarının hem bu yakınlaşması hem de 20. yüzyıl başında ilişkilerin kopma noktasına gelişi Türk romanına konu olur. İki toplum arasındaki tarihsel ilişkinin seyrini romanlarda sürmek mümkündür. Ermeni-Türk ilişkilerinin tarihine paralel biçimde Türk romanının ilk örneklerinde Ermeniler “sadık teba” imajına uygundur. 2. Meşrutiyet sonrasında ve 1. Dünya Savaşı ile birlikte yeni bir Ermeni tipi, Türklerle dostluk yerine işgal güçleri ile işbirliği yapan, komitacı Ermeniler romanda görülür. Bu romanlar çoğunlukla Cumhuriyet’ten sonra yazılmıştır. 1990 sonrasında yazılan romanlarda ise, daha çok tehcirin Ermeniler üzerindeki kötü sonuçlarına odaklanan bir bakış açısı vardır. romanı, Ermeniler, Türk-Ermeni ilişkileri, Osmanlı İmparatorluğu, savaş

It is possible to say that although not up to Greeks, Armenians have been mentioned in many works as both a nationality and some novel characters in Turkish novel. In the novels, it stands out not only the rapprochement of the Turkish and Armenian nations whose lifestyles and geography made them closer to each other, but the examination of the relationship which came to completely the breaking point at the beginning of the past century. In this regard, sufficient materials exist to trail almost every detail of the course of the historical relationship between the two nations in novels. In this study, it has been intended to identify the way of reflection of this relationship and the distinctive features of Armenian fiction characters in the process from the emergence of Turkish novel to the present. At the “Introduction” part of the work; Turkish-Armenian relations has been given. Mostly, the novels focusing on relations of the Armenians with the Turks before the Second Constitutional Monarchy and thus dealing with a period that is relatively trouble-free are located in the second chapter. In the third chapter; the novels emphasizing on a new type of Armenian in quest of independence, comitadjis, who emerged after the Second Constitutional Monarchy and with the First World War, come to the fore. These novels are also the novels dealing with and discussing issues such as deportation, the viewpoint of the Committee of Union and Progress towards non-Muslim minorities, etc. In the fourth and the final chapter, the works, the subjects of which are similar to that of the previous two sections, but written after 1990 in respond to political and cultural debates in the world in the context of the Armenian deportation, have been examined. Key Words: Turkish Novel, Armenians, Turkish-Armenian Relations, Ottoman Empire, war
Keywords: Ermeniler_Türk Dili; Roman_Ermeniler; Roman_Türk Dili